Association of PECAM-1 Gene Polymorphisms with Kawasaki Disease in Chinese Children. (23rd April 2017) - Li, Zhuoying; Han, Dong; Jiang, Jie; Chen, Jia; Tian, Lang; Yang, Zuocheng
Abstract : Kawasaki disease (KD) is an acute systemic vasculitis complicated by development of coronary artery lesions. PECAM-1 is a kind of cell adhesion molecule, which plays an important role in coronary artery disease. The relationship between PECAM-1 gene polymorphisms and their susceptibility to Kawasaki diseases (KD) is still unclear. In our study, we examined the PECAM-1 gene polymorphisms in 44 KD patients and 59 healthy children and revealed the correlation of PECAM-1 gene polymorphisms in KD children with and without coronary artery lesions (CAL).